Prostate shapes on pre-treatment MRI between prostate cancer patients who do and do not undergo biochemical recurrence are different: Preliminary Findings. Issue 1 (December 2017) - Ghose, Soumya; Shiradkar, Rakesh; Rusu, Mirabela; Mitra, Jhimli; Thawani, Rajat; Feldman, Michael; Gupta, Amar C.; Purysko, Andrei S.; Ponsky, Lee; Madabhushi, Anant
Abstract Early identification of PCa patients at risk for biochemical recurrence (BCR) post-therapy will potentially complement definitive therapy with either neo- or adjuvant therapy to improve prognosis. BCR post definitive therapy is often associated with disease progression that might cause a bulge in the prostate gland. In this work we explored if an atlas-based comparison approach reveals shape differences in the prostate capsule as observed on pre-treatment T2-weighted MRI between prostate cancer patients who do (BCR + ) and do not (BCR − ) have BCR following definitive therapy. A single center IRB approved study included 874 patients. Complete image datasets, clinically localized PCa, availability of Gleason score, data available for post-treatment PSA and follow-up for at least 3 years in patients without BCR were the inclusion criteria to select 77 patients out of the 874 patients. Further controlling for Gleason score, stage, age and to maintain equal number of cases for theBCR + andBCR − categories, the total number of cases was reduced to 50. Manually segmented prostate capsules were aligned to aBCR − template for statistical comparison between theBCR + andBCR − groups. Statistically significant shape difference between the two groups was observed towards the lateral and the posterior sides of prostate.